The Relationship between Interpersonal Communication, Empathy, and Happiness among Secondary School Students in Villavicencio, Chile - Koryn Bernal; Yorman; Ramiro Lobaton; Benard O. Kogola; Lina Maria Carreno Parra (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Adolescence is a critical developmental period in which social interactions play a fundamental role in shaping emotional well-being. This study investigates the relationship between interpersonal communication, empathy, and happiness among secondary school students in Villavicencio, Chile. Drawing on a quantitative correlational design, data were collected from students enrolled in public and private high schools using validated self-report questionnaires measuring interpersonal communication skills, empathy, and subjective happiness. Descriptive statistics, Pearson correlation analysis, and multiple regression were employed to examine the relationships among variables. The findings reveal that interpersonal communication and empathy are positively and significantly correlated with students’ happiness. Interpersonal communication showed a strong association with empathy, indicating that effective communication skills facilitate greater emotional understanding and responsiveness toward others. Regression analysis further demonstrated that both interpersonal communication and empathy significantly predicted happiness, with empathy partially mediating the relationship between communication and well-being. These results suggest that adolescents’ happiness is closely linked to their capacity to communicate effectively and to engage empathetically within their social environment. The study contributes to the growing body of literature on social-emotional development in education by providing empirical evidence from a Latin American context, which remains underrepresented in existing research. Practically, the findings highlight the importance of integrating social-emotional learning programs into secondary education to foster communication skills and empathy as key determinants of student well-being. Despite its contributions, the study is limited by its cross-sectional design and reliance on self-report measures. Future research is encouraged to employ longitudinal and intervention-based approaches to further explore causal mechanisms and practical applications in diverse educational settings.